The Construction of Mathematical Meaning in Elementary School Students: Pestalozzi's Philosophical Perspective in the Modern Learning Era - Buyung Buyung (Journal of Educational Review and Research, 2024)
This study aims to analyze the construction of mathematical meaning in elementary school students through the perspective of Johann Heinrich Pestalozzi's philosophy of education and its relevance to modern learning. This study is motivated by the tendency of elementary mathematics learning which is still dominated by procedural, symbolic, and memorization approaches, so that it does not provide space for concrete experiences and the process of building meaning. The research uses a qualitative method of literature study by analyzing Pestalozzi's primary work, cognitive development theory, contemporary mathematical pedagogical literature, and historical-philosophical research related to concrete learning. Data are analyzed through content analysis techniques and philosophical-hermeneutic interpretation to interpret Pestalozzi's basic principles and relate them to modern mathematical learning practices. The results of the study show that the principles of "head, heart, and hand", learning through observation, and the use of concrete objects provide a strong foundation for meaningful, gradual, and developmentally appropriate mathematics learning. The dominance of procedural learning is influenced by test-oriented curriculum, teachers' teaching habits, time pressure, and textbooks that emphasize algorithms. The synthesis of findings resulted in a Pestalozzian-Based Mathematics Learning framework that includes three elements: contextualization of experiences, manipulative-representational activities, and dialogue and reflection. This study concludes that Pestalozzi's thinking is very relevant for the renewal of elementary mathematics pedagogy, because it places concrete experiences, humanization of learning processes, and the construction of meaning as the core of modern mathematics education